The relationship between patient-centered care and outcomes in specialist drug and alcohol treatment: A systematic literature review. Issue 2 (2nd April 2020) - Davis, Esther L.; Kelly, Peter J.; Deane, Frank P.; Baker, Amanda L.; Buckingham, Mark; Degan, Tayla; Adams, Sarah
Abstract: Background: Patient-centered care is strongly advocated as a key for improving the quality of healthcare. Research examining the impact of patient-centered care in healthcare has concluded that there are demonstrable albeit inconsistent relationships between patient experience, quality of care, and healthcare outcomes. Knowledge of the impact of patient-centered care in the treatment of substance use disorder is limited. The aim of this review was to assess relationships between indicators of patient-centered care (satisfaction and patient-reported experience measures) and patient outcomes (substance use, psychological wellbeing, and service use) among people attending treatment for substance use disorder. Methods: A systematic electronic literature search of a range of databases was conducted with variations of the search terms 'patient-centered care', 'substance use disorders', and residential or community specialist 'treatment'. The populations, interventions and outcomes were summarized and described according to the PRISMA statement. Results: A total of 25 articles were identified, of which only five included a patient-centered indicator other than satisfaction. Indicators of patient-centered care showed a generally positive association with improved outcomes, particularly between satisfaction with treatment and substance use. Nonetheless, mixed and contradictory results were not uncommon, more so for psychological wellbeing outcomes. Conclusions: There were demonstrable relationships between patient-centered indicators and outcomes for people receiving treatment for substance use disorder. However, conclusions are limited due to underrepresentation of patient-reported experience measures. Further research in the area is needed involving comparisons of patient centered indicators with outcomes and use of patient-reported experience measures together with satisfaction. Registration number: CRD42018092829